Training on product development made from fresh cow's milk for housewives in Kemuning Lor Village, Jember - Firda Agustin; Ayu Febriyatna; Ratih Putri Damayati (Community Empowerment, 2022)
Fresh milk is a liquid that comes from a clean, healthy cow's udder and is obtained through proper milking; it has not undergone any processing other than cooling to preserve its natural composition. Fresh cow's milk is rich in macro and micro nutrients, namely protein, vitamins and minerals. The purpose of this community service is to increase the knowledge and skills of housewives in Kemuning Lor Village, Arjasa District, Jember Regency. The process involves the presentation of the material, instruction in making milk candies and crispy fried milk, and evaluation. According to the post-test results, the participants were able to name the ingredients needed to make milk candy and crispy fried milk, and there were no obstacles or suggestions in the manufacturing process. Participants could also independently make milk candy and crispy fried milk.